Transformation of Islamic Education Curriculum Evaluation Management in the Digital Era - Choirul Astrian Saputra; Syauqi Musfirah Musfirah Daud Pisba; Putri Nadina Shafira Islamy; Fatimah Azzahra; Popi Puadah; Madian Muhammad Muchlis (Al-Ulum: Jurnal Pendidikan Islam, 2026)
The transformation of the evaluation management of the Islamic Religious Education (PAI) curriculum in the digital era is an important effort to improve the quality of learning that is adaptive to technological developments. This study aims to analyze the form of transformation of the PAI curriculum evaluation, identify challenges, and examine their implications on the quality of learning. The method used is a qualitative approach with the type of library research through the review of relevant scientific literature. Data analysis is carried out using content and thematic analysis techniques. The results of the study show that the transformation of the evaluation of the PAI curriculum is characterized by a shift from conventional methods to digital-based systems, such as Learning Management System (LMS), Computer-Based Test (CBT), and data-based evaluation. This transformation increases efficiency, objectivity, and allows for continuous evaluation. However, challenges still arise, such as limited infrastructure, low digital literacy, and readiness of human resources. Overall, this transformation has a positive impact on realizing innovative, adaptive, and student-centered learning.